Negative Effects of Stromal Neutrophils on T Cells Reduce Survival in Resectable Urothelial Carcinoma of the Bladder - Yang, Meihua; Wang, Bo; Hou, Weibin; Yu, Hao; Zhou, Bingkun; Zhong, Wenlong; Liu, Zhuowei; Li, Jinqing; Zeng, Hong; Liu, Cheng; Qin, Haide; Lin, Tianxin; et al. (Frontiers in Immunology, 2022)
Urothelial carcinoma of the bladder (UCB) is a major type of bladder cancer with a distinct tumor microenvironment (TME). Although neutrophils are the main component of myeloid cells in the TME, the clinical significance and function of the neutrophils remain unclear in UCB. Here, we observed CD66b+ neutrophils were predominantly enriched in the stroma of UCB tissues and their levels emerged as an independent prognostic factor for overall survival (P = 0.006, n = 237), and were positively associated with age (P = 0.033), tumor stage (P < 0.0001), nodal metastasis (P = 0.045), and histological grade (P < 0.0001). Furthermore, we found that CD66b+ neutrophils were frequently co-localized with CD4+ T cells (R=0.35, P<0.0001), CD8+ T cells (R=0.52, P<0.0001) and cleaved caspase 3+ apoptosis cells (R=0.44, P < 0.0001) in the stroma of UCB tissue. In addition, better effects of T cells on patients’ survival were markedly reduced by neutrophils and T cells co-infiltration. Moreover, we confirmed bladder tumor cell supernatant treated neutrophils suppressed T cell proliferation and activation, and promoted T cell apoptosis through GM-CSF induced PD-L1 in vitro. The expression of PD-L1 by neutrophils was also detected in fresh UBC tissues by using flow cytometric analysis. These data suggested that stromal CD66b+ neutrophils may potentially represent a reliable marker of poor prognosis for UCB patients, and neutrophils might play an immunosuppressive role on T cell immunity partially via the expression of PD-L1.